Does Cash Waqf Linked Sukuk Sustain for State Budget Financing After Covid-19 Pandemic? - Kaila, Kennya Shafaa; Pribadi, Yanuar (Polytechnic of State Finance STAN, 2025)
The COVID-19 outbreak, which began in early 2020, necessitated significant adjustments to the fiscal policies of the Republic of Indonesia, particularly in the state budget structure. In response to the economic pressures induced by the pandemic, the government was compelled to finance its budget deficit through debt issuance. Effective and efficient debt management is essential, requiring financing to be secured at minimal cost while maintaining manageable risk levels. One of the financial instruments introduced during this period was the Cash Waqf Linked Sukuk (CWLS), a novel government security launched in 2020. This study employs a descriptive qualitative approach to evaluate the external and internal factors influencing CWLS through SWOT analysis. The findings suggest that while CWLS presents an opportunity to enhance the government's debt instruments, expanding its implementation remains challenging despite Indonesia’s significant cash waqf potential. Key obstacles include limited public literacy regarding waqf, insufficient competence among nazhirs (waqf managers), and inadequate public communication strategies related to waqf. These factors constrain the potential of waqf as a viable mechanism for strengthening government financing through debt instruments.